(untitled) (Conferencea, 2022)
This article discusses the international experience in effective human resource management, the features of the Japanese approach to management, the main aspects leading to the best results of work and production in the organization. Based on the analysis, recommendations were made to improve the working climate and corporate spirit in national organization.